The Analysis of Cooperation Principles Use on Podcast of Denny Sumargo and Jansen Manangsang: Navigating Controversy A Gricean Analysis of Jansen Manansang Statements on Curhat Bang - Nabilah Siti Haniyah; Nurul Nabila Lubis; Nisa Angelina Agustin Silitonga; Meisuri Meisuri (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
In the digital era, podcasts have emerged as a powerful medium for in-depth conversations that allow speakers to address complex social, personal, and controversial issues. This study aims to analyze how Grice's Cooperative Principles are adhered to, flouted, or violated in Jansen Manangsang's episode on CURHAT BANG. Using a qualitative descriptive approach, selected transcripts will be examined to uncover patterns of conversational behavior that reveal how meaning is constructed and concealed in emotionally intense digital communication. The research highlights the complexity of pragmatic interpretation and underscores the importance of pragmatics theory in analyzing real-life, emotionally charged conversations in digital media. This research contributes to digital pragmatics by showing how language in controversial podcasts shapes public perception, manages emotion, and constructs social narratives.